Habitat Selection and Population Density of Diurnal and Nocturnal Lemurs in the Anjozorobe-Angavo Protected Area, Madagascar - Giulia Sassoli; Aurelia Sebastiani; Davide Mirante; Hanitriniaina Raharinirina; Rojotiana N. Rakotoarisoa; N. M. Koloina Rakotoarivelo; Fanomezantsoa L. Ravololoniaina; H. Domohina S. Randrianarisoa; Gabriele Ferraro; S. Jacques Rakotondranary; Timothy M. Eppley; Luca Santini (International Journal of Primatology, 2026)
Primates are among the most threatened mammals globally owing to rapid habitat loss and intense hunting pressure. Among these, lemurs are the taxon with the highest number of species at risk of extinction. Although many lemur species have been surveyed extensively across Madagascar, some taxa and protected areas remain understudied. The Anjozorobe-Angavo Protected Area, a rainforest landscape in the highlands of central-eastern Madagascar, has received relatively little ecological attention and continues to experience deforestation. This study was designed to estimate the population density and habitat selection of diurnal and nocturnal lemur species within La Mananara, a privately owned forest within Anjozorobe-Angavo. We conducted line-transect surveys over a 3-month period, between October and December 2024, and applied distance sampling to estimate species abundance. We also collected data on species detection locations and established vegetation plots to characterize habitat structure and evaluate species-specific habitat associations through resource selection functions. We recorded four diurnal and six nocturnal lemur species. Nocturnal species exhibited higher estimated densities and were more frequently encountered in areas with human activity, whereas diurnal species were less abundant and generally showed stronger associations with areas characterized by greater canopy cover and lower anthropogenic disturbance. Our findings underscore the conservation importance of primary forest protection, while also demonstrating the role of edge habitat and human-modified habitats for certain nocturnal taxa. These density estimates represent a quantitative assessment for this area, helping to inform the management of La Mananara, and contributing to broader conservation assessments of lemur populations within this under-characterized protected landscape.

Metabolomic signatures of extreme old age: findings from the New England Centenarian Study - Stefano Monti; Michael S. Lustgarten; Ziwei Huang; Zeyuan Song; Mengze Li; Dylan Ellis; Qu Tian; Luigi Ferrucci; Noa Rappaport; Stacy L. Andersen; Thomas P. Perls; Paola Sebastiani (GeroScience, 2026)

Increased genetic protection against Alzheimer’s disease in centenarians - Harold Bae; Zeyuan Song; Amanat Ali; Takashi Sasaki; Niccolò Tesi; Hannah Lords; Anastasia Leshchyk; Yukiko Abe; Nobuyoshi Hirose; Yasumichi Arai; Nir Barzilai; Erica F. Weiss; et al. (GeroScience, 2025)

SNP rs6543176 is associated with extreme human longevity but increased risk for cancer - Anastasia Gurinovich; Zeyuan Song; Harold Bae; Anastasia Leshchyk; Mengze Li; Hannah Lords; Stacy L. Andersen; Marianne Nygaard; Kaare Christensen; E. Warwick Daw; Konstantin G. Arbeev; Michael R. Brent; et al. (GeroScience, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Cross-platform proteomics signatures of extreme old age - Eric R. Reed; Kevin B. Chandler; Prisma Lopez; Catherine E. Costello; Stacy L. Andersen; Thomas T. Perls; Mengze Li; Harold Bae; Mette Soerensen; Stefano Monti; Paola Sebastiani (GeroScience, 2024)

Modelling PM10 removal in three Italian coastal Metropolitan Cities along a latitudinal gradient - L. Nardella; A. Sebastiani; M. Stafoggia; P.P. Franzese; F. Manes (Ecological Modelling, 2023)

A metabolomic signature of the APOE2 allele - Paola Sebastiani; Zeyuan Song; Dylan Ellis; Qu Tian; Michaela Schwaiger-Haber; Ethan Stancliffe; Michael S. Lustgarten; Cory C. Funk; Priyanka Baloni; Cong-Hui Yao; Shakchhi Joshi; Megan M. Marron; et al. (GeroScience, 2023)

Correction to: Effect of longevity genetic variants on the molecular aging rate - Anastasia Gurinovich; Zeyuan Song; William Zhang; Anthony Federico; Stefano Monti; Stacy L. Andersen; Lori L. Jennings; David J. Glass; Nir Barzilai; Sofiya Millman; Thomas T. Perls; Paola Sebastiani (GeroScience, 2021)

Effect of longevity genetic variants on the molecular aging rate - Anastasia Gurinovich; Zeyuan Song; William Zhang; Anthony Federico; Stefano Monti; Stacy L. Andersen; Lori L. Jennings; David J. Glass; Nir Barzilai; Sofiya Millman; Thomas T. Perls; Paola Sebastiani (GeroScience, 2021)

More nature in the city - G Capotorti; S Bonacquisti; L Abis; I Aloisi; F Attorre; G Bacaro; G Balletto; E Banfi; E Barni; F Bartoli; E Bazzato; M Beccaccioli; et al. (Plant Biosystems, 2020)

Patterns of multi-domain cognitive aging in participants of the Long Life Family Study - Paola Sebastiani; Stacy L. Andersen; Benjamin Sweigart; Mengtian Du; Stephanie Cosentino; Bharat Thyagarajan; Kaare Christensen; Nicole Schupf; Thomas T Perls (GeroScience, 2020)

Association of hypnotizability and deep sleep: any role for interoceptive sensibility? - Francesca Diolaiuti; Maria Paola Tramonti Fantozzi; Marco Di Galante; Paola D’Ascanio; Ugo Faraguna; Laura Sebastiani; Enrica L. Santarcangelo (Experimental Brain Research, 2020)

Heterogeneity of healthy aging: comparing long-lived families across five healthy aging phenotypes of blood pressure, memory, pulmonary function, grip strength, and metabolism - Megan M. Marron; Mary K. Wojczynski; Ryan L. Minster; Robert M. Boudreau; Paola Sebastiani; Stephanie Cosentino; Bharat Thyagarajan; Svetlana V. Ukraintseva; Nicole Schupf; Kaare Christensen; Mary Feitosa; Thomas Perls; et al. (GeroScience, 2019)

Recent developments in olive (Olea europaea L.) genetics and genomics: applications in taxonomy, varietal identification, traceability and breeding - L. Sebastiani; M. Busconi (Plant Cell Reports, 2017)

Genetic polymorphism of APOB is associated with diabetes mellitus in sickle cell disease - Xu Zhang; Wei Zhang; Santosh L. Saraf; Mehdi Nouraie; Jin Han; Michel Gowhari; Johara Hassan; Galina Miasnikova; Adelina Sergueeva; Sergei Nekhai; Rick Kittles; Roberto F. Machado; et al. (Human Genetics, 2015)

Brain Responses to Emotional Stimuli During Breath Holding and Hypoxia: An Approach Based on the Independent Component Analysis - Danilo Menicucci; Fiorenzo Artoni; Remo Bedini; Alessandro Pingitore; Mirko Passera; Alberto Landi; Antonio L’Abbate; Laura Sebastiani; Angelo Gemignani (Brain Topography, 2014)

Molecular studies in olive (Olea europaea L.): overview on DNA markers applications and recent advances in genome analysis - T. Bracci; M. Busconi; C. Fogher; L. Sebastiani (Plant Cell Reports, 2011)

Physiological and productive responses of Olea europaea L. cultivars Frantoio and Leccino to a regulated deficit irrigation regime - R. D'andria; A. Lavini; G. Morelli; L. Sebastiani; R. Tognetti (Plant Biosystems, 2009)

In vitro olive ( Olea europaea L.) cvs Frantoio and Moraiolo microshoot tolerance to NaCl - T. Bracci; A. Minnocci; L. Sebastiani (Plant Biosystems, 2008)

Variation in mesophyll anatomy and photosynthetic capacity during leaf development in a deciduous mesophyte fruit tree (Prunus persica) and an evergreen sclerophyllous Mediterranean shrub (Olea europaea) - S. Marchi; R. Tognetti; A. Minnocci; M. Borghi; L. Sebastiani (Trees, 2008)

Deficit irrigation and fertigation practices in olive growing: Convergences and divergences in two case studies - R. Tognetti; A. Morales-Sillero; R. D'Andria; J. E. Fernández; A. Lavini; L. Sebastiani; A. Troncoso (Plant Biosystems, 2008)

Effects of tannery waste on growth dynamics and metal uptake in Salix alba L - G. Giachetti; L. Sebastiani (Plant Biosystems, 2007)

RAPD-derived, PCR-based mitochondrial markers for Larix species and their usefulness in phylogeny - Vladimir L. Semerikov; Giovanni G. Vendramin; Federico Sebastiani; Martin Lascoux (Conservation Genetics, 2006)

Chloroplast DNA phylogeography of European ashes, Fraxinus sp. (Oleaceae): roles of hybridization and life history traits - M. HEUERTZ; S. CARNEVALE; S. FINESCHI; F. SEBASTIANI; J. F. HAUSMAN; L. PAULE; G. G. VENDRAMIN (Molecular Ecology, 2006)
We investigated range‐wide phylogeographic variation in three European ash species ( Fraxinus sp., Oleaceae). Chloroplast DNA (cpDNA) microsatellites were typed in the thermophilous Fraxinus angustifolia and Fraxinus ornus and the observed haplotypes and the geographic distribution of diversity were compared to cpDNA data previously obtained in the more cold‐tolerant Fraxinus excelsior . We found wide‐ranging haplotype sharing between the phylogenetically close F. angustifolia and F. excelsior , suggesting hybridization (i) in common glacial refuges in the Iberian Peninsula, northern Italy, the eastern and/or Dinaric Alps and the Balkan Peninsula, and/or (ii) during postglacial recolonization. The data allowed us to propose additional glacial refuges for F. angustifolia in southern Italy and in Turkey, and populations from the latter region were particularly polymorphic. There was evidence for refuge areas in Italy, the Balkan Peninsula and Turkey for F. ornus , which did not share any single chloroplast haplotype with the other species. In both F. angustifolia and F. ornus , cpDNA diversity ( h S = 0.027 and h S = 0.009, respectively) was lower and fixation levels ( G ST = 0.964 and G ST = 0.983, respectively) higher than in sympatric F. excelsior ( h S = 0.096, G ST = 0.870). These diversity patterns could be due to temperature tolerance or the demographic history.

Kinematic strategies for lowering of upper limbs during suggestions of heaviness: a real-simulator design - E. L. Santarcangelo; E. Cavallaro; S. Mazzoleni; E. Marano; B. Ghelarducci; P. Dario; S. Micera; L. Sebastiani (Experimental Brain Research, 2005)

Molecular differentiation of the Old World Culicoides imicola species complex (Diptera, Ceratopogonidae), inferred using random amplified polymorphic DNA markers - F. Sebastiani; R. Meiswinkel; L. M. Gomulski; C. R. Guglielmino; P. S. Mellor; A. R. Malacrida; G. Gasperi (Molecular Ecology, 2001)
Samples of seven of the 10 morphological species of midges of the Culicoides imicola complex were considered. The importance of this species complex is connected to its vectorial capacity for African horse sickness virus (AHSV) and bluetongue virus (BTV). Consequently, the risk of transmission may vary dramatically, depending upon the particular cryptic species present in a given area. The species complex is confined to the Old World and our samples were collected in Southern Africa, Madagascar and the Ivory Coast. Genomic DNA of 350 randomly sampled individual midges from 19 populations was amplified using four 20‐mer primers by the random amplified polymorphic DNA (RAPD) technique. One hundred and ninety‐six interpretable polymorphic bands were obtained. Species‐specific RAPD profiles were defined and for five species diagnostic RAPD fragments were identified. A high degree of polymorphism was detected in the species complex, most of which was observed within populations (from 64 to 76%). Principal coordinate analysis (PCO) and cluster analysis provided an estimate of the degree of variation between and within populations and species. There was substantial concordance between the taxonomies derived from morphological and molecular data. The amount and the different distributions of genetic (RAPD) variation among the taxa can be associated to their life histories, i.e. the abundance and distribution of the larval breeding sites and their seasonality.

Intron size polymorphism of the Adh 1 gene parallels the worldwide colonization history of the Mediterranean fruit fly, Ceratitis capitata - L. M. GOMULSKI; K. BOURTZIS; S. BROGNA; P. A. MORANDI; C. BONVICINI; F. SEBASTIANI; C. TORTI; C. R. GUGLIELMINO; C. SAVAKIS; G. GASPERI; A. R. MALACRIDA (Molecular Ecology, 1998)
The exon‐primed intron‐crossing (EPIC) PCR technique was used to analyse the size variation at the first intron of the Ceratitis capitata Adh 1 gene. A total of 27 samples from 16 natural populations was analysed from five geographical regions in the species range: Africa, Mediterranean Basin, Latin America, Hawaii and Australia. The Adh 1 first intron varies extensively in length with at least 18 size variants ranging from 1400 bp to 3450 bp. These variants can be grouped into four distinct size categories: short, medium, long and very long. The majority of these variants are present only in the African populations. Only a subset of the ancestral variants appear to have succeeded in migrating from Africa during the medfly colonization process. The medfly population structure inferred from the intron size polymorphism is congruent with that observed from the analysis of allozyme variation. The geographical dispersal of the medfly from its source area is associated with a gradual and great reduction in intron variability which parallels the trend of decreasing variability evaluated at 26 biochemical loci. The intron phylogenetic tree is in agreement with allozyme data in portraying the dynamic population history of the medfly. Stochastic evolutionary forces such as drift, bottleneck effects and migration seem to have played the major roles in the dispersion pattern of Adh 1 intron variation during the colonization of the medfly.